Gender Relations and Female Agency in Claire Keegan’s Antarctica - Morales-Ladrón, Marisol (Studia Anglica Posnaniensia, 2021)
Claire Keegan is one of the most prominent voices within the contemporary Irish short story panorama. Internationally acclaimed, her prose has been praised for its frank and bitter portrayal of a rural world, whose outdated values, no matter how anchored in the past they might be, still prevail in a modern milieu. Keegan’s unsympathetic views on society, mainly on the Catholic Church and the family, are the main targets of her harsh criticism. Issues like gender and sexuality, two social constructs with which to validate an uneven distribution of power, constitute the pillars of most of her plots. Bearing these aspects in mind, my proposal focuses on the analysis of Keegan’s first collection of short stories, Antarctica (1999), in light of gender relations and female agency, in an attempt to find patterns of – often thwarted – female emancipation in the context of the rapid changes of a society that is still adjusting to a globalised world. This article will also engage in the discussion of her second collection, Walk the Blue Fields (2007), and her long short story Foster (2010).